Physical activity and depressive symptoms among college students: positive mental health as a mediator - Chen, Yizhou; Zhang, Jie (Frontiers in Psychology, 2026)
IntroductionNumerous studies confirm that physical activity alleviates depressive symptoms in college students, but the underlying mechanisms remain unclear. This study aimed to explore whether positive mental health mediates the relationship between physical activity and depressive symptoms.MethodsA cross-sectional online survey was conducted among 3,140 college students, who completed self-report questionnaires on physical activity, positive mental health, and depressive symptoms. Data were analyzed using SPSS 29.0 and AMOS 29.0 with structural equation modeling.ResultsResults showed 69.39% of participants had low physical activity, and 19.24% reported clinically significant depressive symptoms. The findings showed significant correlations among the three variables, with positive mental health strongly associated with reduced depressive symptoms. Bootstrap mediation analysis (5,000 iterations) confirmed a mediating role of positive mental health.DiscussionThis study advances theoretical understanding by identifying positive mental health as one possible pathway linking physical activity to better mental health outcomes. Due to the effect is small, the results should be interpreted cautiously. The findings provide conceptual support for integrating positive mental health promotion into physical activity-based interventions targeting college students’ depressive symptoms, with no causal inferences implied due to the cross-sectional design.